Phase I/II study of weekly paclitaxel and carboplatin with concurrent radiation therapy in locally advanced non- small-cell lung cancer: Kansai Clinical Oncology Group T0401. Issue 4 (2017) - Takamatsu, Kazufumi; Marumo, Satoshi; Takagi, Takehisa; Fukui, Motonari; Komuta, Kiyoshi; Mio, Tadashi; Hirabayash, Masataka
No abstract available